2021
DOI: 10.1007/s12210-021-01024-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of water hyacinth growth and its role in heavy metals accumulation from unoperated old Ganga canal at Haridwar, India

Abstract: The present study aimed to investigate the annual potential of water hyacinth (WH; Eichhornia crassipes) macrophyte in an un-operated/abandoned stretch of the upper Ganga canal at Haridwar, India. The study covered a 25 km long and 100 m wide stretch of the old Ganga canal which exhibits a huge WH growth every year. For this, standard field and laboratory methods were adopted to estimate the WH biomass density (Kg/m 2 ), and heavy metals dynamics between canal water and macrophyte biomass. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Phyto-remedial capability of water hyacinth for heavy metals namely Pb, Cd, Hg, and Zn scavenging also demonstrated by Sasidharan et al [49]. Similar results are also reported by Kumar et al [50]. Moreover, the ANOVA values for physico-chemical levels of EC, BOD, COD, nitrate, and phosphate were found to be significant (p < 0.05) for the different water hyacinth levels in the lake.…”
Section: The Effect Of Water Hyacinth On the Physico-chemical Levels ...supporting
confidence: 86%
“…Phyto-remedial capability of water hyacinth for heavy metals namely Pb, Cd, Hg, and Zn scavenging also demonstrated by Sasidharan et al [49]. Similar results are also reported by Kumar et al [50]. Moreover, the ANOVA values for physico-chemical levels of EC, BOD, COD, nitrate, and phosphate were found to be significant (p < 0.05) for the different water hyacinth levels in the lake.…”
Section: The Effect Of Water Hyacinth On the Physico-chemical Levels ...supporting
confidence: 86%
“…Although relatively complex, the use of regression models is a valuable approach that facilitates the prediction of metal contents in plant tissues according to several soil variables, i.e., metal contents, pH and OM content (Shaltout et al 2021). It should be confirmed that the created model offers a good fit for the pertinent application; relevant mathematical parameters to achieve such confirmation including R 2 , ME, MANE, MNB, and p values (Novotná et al 2015;Kumar et al 2019Kumar et al , 2021. In this study, a good fit was determined for all the established regression paradigms for the majority of metals in the different components of forage sorghum.…”
Section: Discussionsupporting
confidence: 51%
“…The principal factors utilized to establish the metal contents in the plant tissues were pH, EC and OM content (Yang et al 2013;Novotná et al 2015). The model's general equation can be written as: The following parameters were utilized to evaluate the efficacy, robustness and bias of the model: coefficient of determination (R 2 ), model efficiency (ME), mean normalized average error (MNAE), and mean normalized bias (MNB) (Kumar et al 2019(Kumar et al , 2021. These measures can be expressed as follows (Novotná et al 2015):…”
Section: Discussionmentioning
confidence: 99%
“…In this context, various aquatic plants such as water ferns (Azolla spp. ), water hyacinth (Eichhornia crassipes), and water lettuce (Pistia stratiotes), etc., have shown a high potential for remediation of a wide range of pollutants [5][6][7]. Previous reports pointed out that an increase in produced plant biomass was underscored proving again the success of this type of phytoremediation aiming for a safer environment [8].…”
Section: Introductionmentioning
confidence: 99%